Measurement and simplified numerical prediction of effective thermal conductivity of open-cell ceramic foams at high temperature. (November 2016) - Mendes, Miguel A.A.; Goetze, Pitt; Talukdar, Prabal; Werzner, Eric; Demuth, Cornelius; Rössger, Philip; Wulf, Rhena; Gross, Ulrich; Trimis, Dimosthenis; Ray, Subhashis
Highlights: Effective Thermal Conductivity (ETC) of ceramic foams measured with TPS technique. ETC of ceramic foams measured and predicted at ambient and high temperatures. ETC predicted using model with coupled conduction–radiation heat transfer. Model parameters obtained based on 3D CT-scan images of the real foam structure. Performance of simplified model is compared with measurements. Abstract: In the present article, the effective thermal conductivity (ETC) of 10 ppi open-cell ceramic foams is measured at temperatures ranging from 22 °C to 750 °C using the transient plane source (TPS) technique. The detailed morphology of the foam structures is reconstructed from 3D CT-scan images and their structural analysis is carried out using a volume image processing tool. The experimental results are compared with the predictions of directional ETC, obtained using a simplified 1D homogeneous model that considers coupled conduction–radiation heat transfer. The parameters, required by the model, are evaluated based only upon the information that could be extracted from 3D CT-scan images under certain simplifying assumptions. It can be concluded that the predictions of ETC for the present ceramic foam samples clearly correlate with the geometric parameters obtained from their structural analysis. It is also observed that the estimated microscopic porosity of the foam, which is not captured by 3D CT-scan images, has considerable influence on the reconstructed foam structure and hence on the predicted ETC. The predictions of ETC in the measured direction, obtained after the proposed directional averaging, compare extremely well with TPS measurements for the complete range of investigated temperatures. This suggests that the measurements of ETC, obtained employing TPS technique, are the directionally averaged representations of ETC in three perpendicular directions. The present investigation also clearly demonstrates the potential of the simplified modeling approach for characterizing even the directional ETC of open-cell ceramic foams, based primarily on their structural information.